Detecção de Histophilus somni (Haemophilus somnus) no sêmen bovino mediante reação em cadeia pela polimerase (PCR) - Dias, Francisca Elda Ferreira (2014)
The present study evaluated the use of PCR for Histophilus somni detection in bovine semen. Semen samples were experimentally infected with H. somni at dilutions ranging from 107 to 101 bacteria/mL and subjected to DNA extraction by the phenol/chloroform method, followed by PCR amplification. The amplification products were analyzed by electrophoresis in 8% acrylamide gel. The oligonucleotide primers used yielded an amplification fragment of 400 base pairs from the bacterial DNA. Positive amplification was obtained even for the 101 bacteria/mL dilution. PCR proved to be an efficient method for the detection of H. somni. The results obtained in this study have brought relevant information for the diagnosis of H. somni, justifying the need for the diagnosis of this bacterium in bulls, especially in semen samples that should be free of contamination. The PCR method has shown to be a useful tool for the quality control of semen produced in artificial insemination centers.